Factors Related To The Incidence Of Stunting In Toddlers Aged 24-59 Months In The Region Work Of UPT Puskesmas Sawah Besar Central Jakarta - Ernawati, Ernawati; Yurita Mailintina; Khalida Ziah Sibualamu; Fitri adella; Keisha Ayu (Jurnal EduHealth, 2024)
The incidence of stunting in toddlers is one of the nutritional problems globally. Based on UNICEF data 2012-2018, the prevalence of stunting in the world reached 28%, in Eastern and Southern Africa by 40%, and in South Asia by 38%. When compared to the limit of "non-public health problem" according to the WHO for stunting problems of 20%, almost all countries in the world experience public health problems. The incidence of stunting in toddlers is more common in developing countries. This is evidenced by the number of stunting prevalence in toddlers in developing countries of 30%. Children will be stunted in their growth due to a lack of adequate food intake and recurrent infectious diseases that cause increased metabolic needs and reduced appetite. This can lead to increased malnutrition in children. This situation will make it more difficult to overcome growth disorders that ultimately have the opportunity to cause stunting. The purpose of this study is to find out the factors related to the incidence of stunting in toddlers aged 24-59 months in the Working Area of the Sawah Besar Health Center, Central Jakarta.   This type of research is quantitative with a Cross-Sectional design. The research approach used is a quantitative approach, namely the use of questionnaires and survey research techniques which are components of quantitative research. The results of the analysis show that the majority of mothers are in productive age, but there are also young and old mothers who face different challenges in parenting. The mother's education level is generally low, affecting parenting and nutrition. Preschool-age children are predominantly female, and most have normal height and weight, although some are at risk of stunting, especially with short height or low birth weight. The majority of children receive complementary foods as recommended, although a small number get them too early. Mothers' knowledge of nutrition is still mixed, with many lacking understanding, indicating the need for intensive education. Educational factors, feeding patterns, birth weight, and maternal knowledge are closely related to the risk of stunting, requiring strategic interventions to improve children's health.